Pharmacokinetics of pyronaridine in malaria patients - Feng Zheng; Wu Zu-Fan; Wang Cui-Ying; Jiang Nai-Xiong (Acta Pharmacologica Sinica, 2016)
Pyronaridine (PND), an anti-malarial, was first developed in China. Its chemical name is 2-methoxy-7-chloro-10-[3’,5’-bis (pyrolidinyl-1-methyl) -4’-hydroxy-anilino]benzo-[b]-1,5-naphthyridinc tetraphosphate. Its pharmacokinetics after im and po to malaria (Plasmodium falciparum and P vivax) patients were studied. The whole blood concentrations were measured periodically for 72 h, using a sensitive and specific spectrofluorometric method. The concentration-time data were analyzed with a modified NONLIN computer program on IBM-PC microcomputer. Four patients were given a single dose (204 mg) im, and the concentration-time course was adequately fitted to a linear 2-compartment open model. There were considerable variations in the estimated kinetic parameters, but the differences did not appear to be related to the dosage. It was rapidly absorbed with a mean Cmax of 525 ng/ml at Tmax 0.66 h. The t was 63±5 h. The mean Vc and Vss were 11.1 and 71.5 L/kg, respectively, t(1/2β) indicating an extensive tissue distribution. After a single oral dose of 0.6 g PND in enteric-coated tablets (3 patients) or in capsules (3 patients), the t(1/2β)were 65±6 and 63±6h; mean Tmax, 14.0 and 4.7h; Cmax, 127.5 and 255.3 ng/ml, respectively. In comparison with im, oral PND was much less bioavailable. The relative extents of absorption for tablets and capsules were found to be 19±7 and 32±7%，respectively. It was shown that PND oral formulation in current use should be improved to increase its bioavailability.